Intermittent Hypoxia in Childhood: The Harmful Consequences Versus Potential Benefits of Therapeutic Uses - Serebrovskaya, Tatiana V.; Xi, Lei (Frontiers in Pediatrics, 2015)
Intermittent hypoxia often occurs in early infancy in both preterm and term infants and especially at 36 to 44 weeks postmenstrual age. These episodes of intermittent hypoxia could result from sleep-disordered breathing or may be temporally unrelated to apnea or bradycardia events. There are numerous reports indicating adverse effects of intermittent hypoxia on development, behavior, academic achievement and cognition in children with sleep apnea syndrome. It remains uncertain the exact causative relationship between the neurocognitive and behavioral morbidities and intermittent hypoxia and/or its associated sleep fragmentation. On the other hand, well-controlled and moderate intermittent hypoxia conditioning/training has been used in sick children for treating their various forms of bronchial asthma, allergic dermatoses, autoimmune thyroiditis, cerebral palsy, and obesity. This review article provides an updated and impartial analysis on the currently available evidence in supporting either side of the seemingly contradictory scenarios. We wish to stimulate a comprehensive understanding of such a complex physiological phenomenon as intermittent hypoxia, which may be accompanied by other confounding factors (e.g. hypercapnia, polycythemia), in order to prevent or reduce its harmful consequences, while maximize its potential utility as an effective therapeutic tool in pediatric patients.